Leaving no one behind: lessons on rebuilding health systems in conflict and crisis-affected states - Martineau, Tim; McPake, Barbara; Theobald, Sally; Raven, Joanna; Ensor, Tim; Fustukian, Suzanne; Ssengooba, Freddie; Chirwa, Yotamu; Vong, Sreytouch; Wurie, Haja; Hooton, Nick; Witter, Sophie (BMJ Glob Health, 2017)
Conflict and fragility are increasing in many areas of the world. This context has been referred to as the ‘new normal’ and affects a billion people. Fragile and conflict-affected states have the worst health indicators and the weakest health systems. This presents a major challenge to achieving universal health coverage. The evidence base for strengthening health systems in these contexts is very weak and hampered by limited research capacity, challenges relating to insecurity and apparent low prioritisation of this area of research by funders. This article reports on findings from a multicountry consortium examining health systems rebuilding post conflict/crisis in Sierra Leone, Zimbabwe, northern Uganda and Cambodia. Across the ReBUILD consortium’s interdisciplinary research programme, three cross-cutting themes have emerged through our analytic process: communities, human resources for health and institutions. Understanding the impact of conflict/crisis on the intersecting inequalities faced by households and communities is essential for developing responsive health policies. Health workers demonstrate resilience in conflict/crisis, yet need to be supported post conflict/crisis with appropriate policies related to deployment and incentives that ensure a fair balance across sectors and geographical distribution.
Keywords: rebuilding health systems; health indicators